Emerging role of long noncoding RNAs in lung cancer: Current status and future prospects. (January 2016) - Tao, Hui; Yang, Jing-Jing; Zhou, Xiao; Deng, Zi-Yu; Shi, Kai-Hu; Li, Jun
Abstract: Lung cancer is the leading cause of cancer-related death worldwide with a 5-year survival rate of less than 15%, despite significant advances in both diagnostic and therapeutic approaches. Combined genomic and transcriptomic sequencing studies have identified numerous genetic driver mutations that are responsible for the development of lung cancer. Importantly, these approaches have also uncovered the widespread expression of "noncoding RNAs" including long noncoding RNAs (LncRNAs), which impact biologic responses through the regulation of mRNA transcription or translation. To date, most studies of the role of noncoding RNAs have focused on LncRNAs, which regulate mRNA translation via the RNA interference pathway. Although many of their attributes, such as patterns of expression, remain largely unknown, LncRNAs have key functions in transcriptional, post-transcriptional, and epigenetic gene regulation. Recent research showed that LncRNAs regulate flowering time in the lung cancer. In this review, we discuss these investigations into long noncoding RNAs were performed almost exclusively in lung cancer. Future work will need to extend these into lung cancer and to analyze how LncRNAs interact to regulate mRNA expression. From a clinical perspective, the targeting of LncRNAs as a novel therapeutic approach will require a deeper understanding of their function and mechanism of action. Graphical abstract: Figure Long noncoding RNAs play a key role in the development of lung cancer. Important alterations encompassing epigenetic changes are Long noncoding RNAs. Long noncoding RNAs control gene expression in lung cancer. Highlights: LncRNAs impact on the development of lung cancer. LncRNAs control the pathological processes of NSCLC and SCLC. LncRNAs mediated epigenetic mechanism in lung cancer.